Verification and evaluation of computer and communication systems : 13th International Conference, VECoS 2019, Porto, Portugal, October 9, 2019, Proceedings /: 13th International Conference, VECoS 2019, Porto, Portugal, October 9, 2019, Proceedings. (2019) - Unknown
No abstract available